2005
DOI: 10.1002/art.21212
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of human stem cells derived from various mesenchymal tissues: Superiority of synovium as a cell source

Abstract: Objective. To compare the properties of human mesenchymal stem cells (MSCs) isolated from bone marrow, synovium, periosteum, skeletal muscle, and adipose tissue.Methods. Human mesenchymal tissues were obtained from 8 donors during knee surgery for ligament injury. After collagenase digestion or gradient-density separation, nucleated cells were plated at an appropriate density for expansion at the maximum rate without colony-to-colony contact. Yield, expandability, differentiation potential, and epitope profile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

70
1,171
11
37

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 1,375 publications
(1,316 citation statements)
references
References 43 publications
(58 reference statements)
70
1,171
11
37
Order By: Relevance
“…In culture, cells expressing Stro-1 À /ALP + accounted for approximately 40% of the population and Stro-1 + /ALP + a further 10%. These values are consistent with early passage cultured cells derived from known MSC sources: trabecular bone explants [17], bone marrow, synovial lining, adipose tissue, muscle, and a single passage of periosteum [35]. More surprising than the osteogenic phenotype of cultured HPDCs in this study was the presence of a consistent and stable Stro-1 + population.…”
Section: Discussionsupporting
confidence: 85%
“…In culture, cells expressing Stro-1 À /ALP + accounted for approximately 40% of the population and Stro-1 + /ALP + a further 10%. These values are consistent with early passage cultured cells derived from known MSC sources: trabecular bone explants [17], bone marrow, synovial lining, adipose tissue, muscle, and a single passage of periosteum [35]. More surprising than the osteogenic phenotype of cultured HPDCs in this study was the presence of a consistent and stable Stro-1 + population.…”
Section: Discussionsupporting
confidence: 85%
“…Osteogenic induction medium consisted of complete culture medium supplemented with 1 nM dexamethasone (ICN Biomedicals Inc., Costa Mesa, CA, USA), 10 mM β-glycerol phosphate and 50 μg/ml ascorbic acid (Wako Pure Chemical Industries), as previously reported [13]. To evaluate the mineralized matrix, cells were fixed with 4% formaldehyde and stained with 1% Alizarin Red S (Sigma-Aldrich) for 10 min.…”
Section: In Vitro Differentiation and Histological Analysismentioning
confidence: 99%
“…More recently, the chondrogenic pellet culture method has frequently been used in analyses of pluripotent mesenchymal progenitor cells from adult human tissues, which are also referred to as mesenchymal stem cells (MSCs) (20,21). Our previous studies of the therapeutic use of MSCs in degenerative articular joint diseases showed that among the various MSC types we examined, human synoviumderived MSCs appeared to be most potent for chondrogenesis (22). Since these differences were detectable even in analyses of cells harboring the same genetic makeup, the results indicate that differences other than genomic sequences contribute to the divergent differentiating potentials for cellular lineage specifications.…”
mentioning
confidence: 99%